A pro-cyclical stock market under a countercyclical monetary policy in a model of endogenous business cycles - Boyan Yanovski (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
During the last 25 years, the stock market in the US has been strongly pro-cyclical in the presence of a counter-cyclical monetary policy. In this paper, we use an endogenous business cycle model to explore the factors contributing to a pro-cyclical stock market. A dynamic expectation structure in the real sector gives rise to a strong non-linearity and is responsible for the emergence of endogenous business cycles in the model. In the context of this model, we find that a timid or ineffective monetary policy allows the stock market to be dominated by the fluctuations of profits in the real sector. We model the potential ineffectiveness of monetary policy in terms of an endogenous risk premium. The model is calibrated to fit key properties of the data. In particular, it can generate a pro-cyclical stock market in the presence of a counter-cyclical monetary policy.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C00; D84; E12; E32; E52; G00; 330; pro-cyclical stock market; Tobin's average Q; endogenous cycles; heterogeneous expectations; monetary policy